Suicide Rate, Depression and the Human Development Index: An Ecological Study From Mexico - Cabello-Rangel, Héctor; Márquez-Caraveo, María Elena; Díaz-Castro, Lina (Frontiers in Public Health, 2020)
Objective To assess the contribution of depression, the human development index (HDI) including the health, education and income index as well as the households structure to the suicide rate in Mexican population from 15 to 49 years old. Methods An ecological cross-sectional study was carried out in people between 15-49 years old. The health index (HI), education index (EI), income index (II) and HDI were constructed. The suicide rate, educational level, per capita income, poverty, and rate of households were collected from official databases. Pearson's correlation coefficient (r) was used to determine the strength between the suicide rate and the per capita income, unemployment, poverty, HI, EI, II, HDI, non-family household, and depression incidence rate. A multiple linear regression model was used to know the association between suicide rates and HDI. Results The suicide rate was 8.76/100,000 inhabitants. The HDI of the 32 Mexican states were low 16%, middle 41%, high 22% and extremely high 13%. A direct and positive intensity relationship between suicide rate and non-family households, was found (r=0.352; p<0.001); on the other hand, the suicide rate is significantly and negatively related to family households with Pearson (r = -0.350; p < 0.001). Conclusion The states of the Mexican Republic with the highest prevalence of non-family households had a positive association with the suicide rate. Based on the result of this study, it is possible to assume that, as the HDI increases, there is a greater possibility of living alone and having suicidal behavior.